Ethnicity, physical activity, and the dietary intake of boarding high school students: A photovoice mixed method study - Aqilah, Syarifah; Taneepanichskul, Nutta (International Journal of Innovative Research and Scientific Studies, 2024)
This study explores the dietary intake of female students and its associated factors to understand their meal experiences in a boarding high school setting through a photovoice study. A mixed-methods study included 60 students in paper-and-pencil assessment and 8 students in photovoice activities. The nutritionist measured the anthropometrics and trained the students to keep multiple 24-hour food records. A linear regression model was used to examine the associations and was complemented by a thematic analysis of the story from the produced photos. The result shows most students were at normal weight, and overnutrition was 26.7%. The mean of students’ total energy, protein, fat, and carbohydrate intake was 1182 kcal, 38.7 g, 64.2 g, and 141.7 g, respectively, lower than national recommendations. Ethnicity and physical activity were found to be associated with students’ dietary intake. In the photovoice study, 14 photos were produced, and six major themes emerged during focus group discussions. Sundanese and less physically active students tended to have higher dietary intakes. To conclude, students were aware of food shortages at school and made efforts to supplement their meals, but appropriate food choices were not made. It is necessary for schools to address students’ meal preferences on school menus, promote healthy food, and provide practical nutritional information.